"Self" in language, culture, and cognition - Lu, Yanying (Cognitive linguistic studies in cultural contexts ;, 2019)
"This book explores socio-cultural meanings of 'self' in the Chinese language through analysing a range of conversations among Chinese immigrants to Australia qualitatively on the topics of individuality, social relationships and collective identity. If language, culture and cognition are major roads, this book is the junction that unites them by arguing that selfhood occurs at their interface. It provides an interdisciplinary approach to unpack manifestations and perceptions of 'self' in the contemporary Chinese diaspora discourse from the perspectives of Sociolinguistics, Cognitive Linguistics and the newly developed Cultural Linguistics. This book not only discusses empirical and theoretical issues on the conceptualisation and communication of social identity in a cross-cultural context, it also reveals how traditional and modern ideas in Chinese culture are interacting with those of other world cultures. Considering the power of language, enduring and emerging beliefs and stances that permeate these speakers' views on their social being and outlooks on life impart their significance in cross-cultural communication and pragmatics"--